Case Report: Kanamycin Ototoxicity and MDR-TB Treatment Regimen - Mantefardo B (Dove Medical Press, 2021)
Bahru Mantefardo,1 Gizaw Sisay2 1Department of Internal Medicine, School of Medicine, College of Medicine and Health Sciences, Dilla University, Dilla, Ethiopia; 2School of Public Health, College of Medicine and Health Sciences, Dilla University, Dilla, EthiopiaCorrespondence: Gizaw Sisay Tel +25191158 0679Email gizsisay@gmail.comIntroduction: Aminoglycosides are ototoxic drugs because they have the ability to destroy the inner ear structures irreversibly. They are used to treat Gram-negative bacterial infections that are aerobic and as a second-line treatment for tuberculosis.Case Presentation: A 40-year-old male from Dilla presented with right side chest pain and cough which is productive of whitish sputum of one-year duration, after investigation the diagnosis of multiple-drug resistant tuberculosis (MDR-TB) was made and the patient was started with a short-term MDR-TB treatment regimen (4– 6 KM-Mf-Pto-Cfz-Z-HH-E/5Mfx-Cfz-Z-E). Two and half months after the initiation of treatment, he developed decreased bilateral hearing ability and he had also vertigo, but this patient has no hearing impairment before the initiation of the anti-TB treatment. Then the diagnosis of sensor neural hearing loss secondary to drug toxicity (kanamycin) was made. Then the treatment was discontinued for four days as a result of ototoxicity and the patient was referred to Yirgalem Hospital for further workup and management.Conclusion: Injectable-containing MDR-TB regimens can cause permanent hearing loss. Hearing loss during treatment for MDR-TB with kanamycin can occur at any time. Systematic monitoring of AEs during and after the end of treatment needs to be strengthened in most TB programs. It is important to monitor for hearing loss and kidney function.Keywords: multiple-drug resistant tuberculosis, aminoglycosides, ototoxicity, Ethiopia, MDRT